2018
DOI: 10.1093/aepp/ppy006
|View full text |Cite
|
Sign up to set email alerts
|

The Income Volatility of U.S. Commercial Farm Households

Abstract: This study uses a newly created panel dataset drawn from the 1997 to 2013 Agricultural Resource Management Survey to provide the first national estimates of income volatility for commercial farm households in the United States. Results show that the income of commercial farm households is substantially more volatile than that of all U.S. households—though the volatility of farm income is not more volatile than income from nonfarm self‐employment. Using a regression analysis, we identify operator, operation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The substantial share of operations that lose money does not imply that that there is an equally large share of unprofitable farms. The income of individual farms often varies substantially from one year to the next because of fluctuations in yields and prices (Key, Prager, and Burns, 2018). Hence, it is not surprising that a substantial share of farms will experience losses in any year-even among large, efficient operations.…”
Section: Resultsmentioning
confidence: 99%
“…The substantial share of operations that lose money does not imply that that there is an equally large share of unprofitable farms. The income of individual farms often varies substantially from one year to the next because of fluctuations in yields and prices (Key, Prager, and Burns, 2018). Hence, it is not surprising that a substantial share of farms will experience losses in any year-even among large, efficient operations.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the expectation, both the distance to the railway station and the 'border of destinations' were negatively correlated to the variable describing the off-farm worker's destination choice. Opposite results were indicated by Alasia et al (2009) (2013) and Key et al (2015) identified that the role of factors concerning the location of farms (namely, the regional characteristics) cannot be neglected in the analysis of factors determining the off-farm income, McNamara and Weiss (2005) referred to the role of environmental aspects. The empirical studies of De Janvry and Sadouled (2001) investigated the urban-rural linkages, namely the number of urban centres.…”
Section: "Environmental" Determinants Of the Off-farm Incomementioning
confidence: 99%
“…The results from the estimation of econometric models indicated that the location of farm households in more productive areas decreased the probability of generating the off-farm income. Key et al (2015) analysed the income instability of farm households in the Continental United States. They used a panel dataset of the Agricultural Resource Management Survey from 1996 to 2013.…”
Section: "Environmental" Determinants Of the Off-farm Incomementioning
confidence: 99%
“…It is getting harder for these farms to be profitable in an economic context marked by deep and continuous changes in global agricultural markets, a steady decrease of the "terms of trade" between agricultural product prices and manufactured goods prices, including inputs from agriculture, strong competition for land grabbing and use-produced by urbanisation, particularly in the form of urban sprawl and infrastructure construction-as well as fast and drastic transformations in agrifood chains, which often make small farmers contractually weaker [1][2][3][4][5]. Furthermore, agricultural income is highly unstable, and farming is a hazardous business due to sudden changes in both yields and prices that are not completely manageable over time [6] and which are driven by production, price, and technological and policy uncertainties [7].…”
Section: Introductionmentioning
confidence: 99%